Endothelin-1 plasma concentrations in depressed patients and healthy controls - Lederbogen, Florian; Hamann-Weber, Bettina; Colla, Michael; Heuser, Isabella; Deuschle, Michael (Neuropsychobiology, 1999)
Depression and cardiovascular morbidity are known to be associated. So far, however, the pathophysiological link between these conditions is unclear. We tested the hypothesis that in depressed hypercortisolemic patients endothelin-1 (ET-1) plasma concentrations are increased and contribute to the cardiovascular risk. Diurnal plasma concentrations of cortisol and ET-1 were measured in 29 healthy controls and 22 depressed patients. ANCOVA did not reveal a significant effect of diagnosis or age upon ET-1 concentrations. However, only in depressed patients, cortisol plasma concentrations tended to be positively related to ET-1 concentrations. We conclude that ET-1 is not increased in depressed patients, but within this group, hypercortisolemia may be associated with increased ET-1 concentrations.